Single domain intracellular antibodies from diverse libraries: emphasizing dual functions of LMO2 protein interactions using a single VH domain. - Tanaka, T; Sewell, H; Waters, S; Phillips, SE; Rabbitts, T (2011)
Interfering intracellular antibodies are valuable for biological studies as drug surrogates and as potential macromolecular drugs per se. Their application is still limited because of the difficulty of acquisition of functional intracellular antibodies. We describe the use of the new intracellular antibody capture procedure (IAC(3)) to facilitate direct isolation of functional single domain antibody fragments using four independent target molecules (LMO2, TP53, CRAF1, and Hoxa9) from a set of diverse libraries. Initially, these have variability in only one of the three antigen-binding CDR regions of VH or VL and first round single domains are affinity matured by iterative randomization of the two other CDRs and reselection. We highlight the approach using a single domain binding to LMO2 protein. Our results show that interfering with LMO2 protein function demonstrates a role specifically in erythroid differentiation, confirm a necessary and sufficient function for LMO2 as a cancer therapy target in T-cell neoplasia and allowed for the first time production of soluble recombinant LMO2 protein by co-expression with intracellular domain antibodies. Co-crystallization of LMO2 and the anti-LMO2 VH protein was successful. These results demonstrate that this third generation IAC(3) offers a robust toolbox for various biomedical applications and consolidates functional features of the LMO2 protein complex, which includes the importance of Lmo2-Ldb1 protein interaction.